Detection of Different Patterns of Genome-Wide Gene Expression Disturbance in Three Nullisomy Lines in Allotetraploid Brassica napus - Shaolin Lei; Bo Wei; Qi Hu; Lang Liu; Feng Yu; Tuo Zeng; Xuye Du; Lei Gu; Hongcheng Wang (Plants)
Aneuploidy-related disruptions are generally tolerated in polyploid plants, which exhibit a greater capacity for genomic compensation. In this study, we utilize allotetraploid Brassica napus as a model and generated three aneuploid variants (NC1, NC2, and NC8) to investigate the phenotypic and transcriptional consequences of chromosome loss. Significant phenotypic variations were observed, with the most notable being a marked dwarfing phenotype in the aneuploid materials compared to the euploid Oro. Transcriptomic analysis revealed widespread alterations in gene expression across the entire genome in the deficient variants. Notably, most of the differentially expressed genes (DEGs) were attributed to trans-acting effects resulting from the deletion of C chromosomes. Deletion of the C chromosomes induced gene expression changes not only on the corresponding chromosomes, but also on the affected genes across other chromosomes. Specifically, in the C1-deleted variant, the average gene expression of the A1 chromosome increased, while the number of expressed genes on other chromosomes decreased. In contrast, for C2 and C8 deletions, the average expression levels of homologous genes decreased, but the number of expressed genes on other chromosomes increased. These findings shed light on the complex compensatory mechanisms that underlie aneuploidy in polyploid plants and provide valuable insights into how plants maintain genomic stability despite chromosomal loss.